The Fracture Toughness and Brittleness of Au doped YBCO Superconductors - Rıfkı Terzioğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2020)
In this work, the effect of Au addition on some mechanical properties of YBCO superconductors are analyzed. Five different samples (undoped, 1%, 5%, 15% and 20%) were prepared using the conventional solid state reaction method. The experimental results of the microhardness measurements are used to obtain the yield strength, Young’s modules, fracture toughness and brittleness index. These mechanical properties mentioned above are extracted by using the proportional specimen resistance (PSR) model. The mechanical properties of the samples were found to be load dependent. The yield strength, Young’s modules, brittleness index and fracture toughness values increase with decreasing test load and decreases with increasing Au content. The possible reasons for the observed degradation in the mechanical properties due to Au addition are discussed.